Geometric abstract painting as a means to enhance creativity in architecture education - Golabi, Maryam (Adaya Press, 2025)
One of the main objectives of architecture education is to foster students' creativity, problem-solving skills, and innovative thinking. This study examines the impact of integrating geometric abstract paintings into an elective course titled Colors and Textures for first-year architecture students, exploring its role in fostering creativity and analytical skills. Various geometric abstract paintings were given to students to analyze them and elucidate the principles and organizational concepts embedded in the compositions. Students were then asked to convert these two-dimensional compositions into three-dimensional models in accordance with established concepts. The finding highlights that engaging with abstract paintings enabled students to develop a deeper understanding of form and composition, facilitating students' comprehension of basic design principles, essential in both architecture and visual arts. The study underscores the effectiveness of this interdisciplinary approach in fostering students' conceptual thinking, critical analysis, and ultimately the architectural design process during the translation of two-dimensional compositions into three-dimensional models.
7th Interdisciplinary and Virtual Conference on Arts in Education-CIVAE-Annual -- MAR 12-13, 2025 -- ELECTR NETWORK
Keywords: architecture education; creativity; geometric abstract paintings